Managing climate change transition risks: another potential role for civil engineers. Issue 5 (9th March 2021) - Vercruysse, Julian; Yates, Kim; Stronati, Davide
Abstract : In addition to the physical risks of climate change, civil engineers also need to consider the transition risks involved in moving towards net zero greenhouse gas emissions. These include enhanced reporting obligations, stigmatisation of polluting industries and shifts in consumer preferences. This paper reports on a study into the potential role of civil engineers in mitigating transition risks, using London's Heathrow airport expansion project as a case study. It concludes that while transition to a net zero economy will create a window of opportunity for civil engineers, additional skills will be needed for them to play a major role.